Intramolecular carbon isotope fractionations of acetate associated with glucose metabolism in Escherichia coli using gas chromatography orbitrap-mass spectrometry (GC Orbitrap-MS) - Youki J. Sato; Juliana K. Drozd; Elliott P. Mueller; Allison A. Baczynski; Alexis Gilbert; Katherine H. Freeman (Organic Geochemistry, 2026)

Comparison of Leptosira concentrations in two rivers within contrasting catchments in a leptospirosis hotspot - R. Thibeaux; P. Genthon; R. Govan; N. Selmaoui-Folcher; A. Peltier; M. Kainiu; M.-E. Soupé-Gilbert; O. Yu; C. Tramier; K. Wijesurriya; C. Goarant (Journal of Contaminant Hydrology, 2026)

Impact of wave-current interaction on Hurricane Ian storm surge simulation - Sieu-Cuong San; Yonggang Liu; Haibo Xu; Robert H. Weisberg; Sebin John; Kaili Qiao; Jason A. Law; Lianyuan Zheng; Steven A. Murawski; Sherryl Gilbert; Gary T. Mitchum; Thomas K. Frazer; et al. (Ocean Modelling, 2026)

Confocal laser endomicroscopy: exploring endometrial image quality in relation to the oestrous cycle of mares - K. Gallacher; L. Woolford; R.O. Gilbert; L.C. Santos; J. McLeod; M. Hebart; G. Ferlini Agne; S. du Preez; K.L. Kind (Journal of Equine Veterinary Science, 2026)

Machine learning-based modeling of groundwater recharge under three climate change scenarios in the Densu Basin of Ghana, West Africa - Gilbert Jesse; Cyril D. Boateng; Jeffrey N.A. Aryee; Marian A. Osei; Michael Baidu; David D. Wemegah; Solomon S.R. Gidigasu; Samuel K. Afful (Groundwater for Sustainable Development, 2026)

Cumulative effects analysis to inform public land management in the United States: key characteristics and legal challenges - Tait K. Rutherford; Tim O. Hammond; Alison C. Foster; Megan A. Gilbert; Travis S. Haby; Richard J. Lehrter; Jennifer K. Meineke; Ella M. Samuel; Sarah K. Carter (Environmental Impact Assessment Review, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Corrigendum to “Rainfall-driven resuspension of pathogenic Leptospira in a leptospirosis hotspot” [Sci. Total Environ. (2024) 168700] - R. Thibeaux; P. Genthon; R. Govan; N. Selmaoui-Folcher; C. Tramier; M. Kainiu; M.-E. Soupé-Gilbert; K. Wijesuriya; C. Goarant (Science of The Total Environment, 2026)

Persistent Genomic Erosion in Whooping Cranes Despite Demographic Recovery - Claudia Fontsere; Samuel A. Speak; Andrew J. Caven; Juan Antonio Rodríguez; Xuejing Wang; Carolina Pacheco; Molly Cassatt‐Johnstone; Georgette Femerling; Brigid Maloney; Jennifer Balacco; Joanna Collins; Ying Sims; et al. (Molecular Ecology, 2025)
Integrating in‐situ (wild) and ex‐situ (captive) conservation efforts can mitigate genetic diversity loss and help prevent extinction of endangered wild populations. The whooping crane ( Grus americana ) experienced severe population declines in the 18th century, culminating in a collapse to ~20 individuals by 1944. Legal protections and conservation actions have since increased the census population from a stock of 16 individuals to approximately 840 individuals, yet the impact on genomic diversity remains unclear. We analysed the temporal dynamics of genomic erosion by sequencing a high‐quality reference genome, and re‐sequencing 16 historical (years 1867–1893) and 37 modern (2007–2020) genomes, including wild individuals and four generations of captive‐bred individuals. Genomic demographic reconstructions reveal a steady decline, accelerating over the past 300 years with the European settlement of North America. Temporal genomic analyses show that despite demographic recovery, the species has lost 70% of its historical genetic diversity and has increased its inbreeding. Although the modern population bottleneck reduced the ancestral genetic load, modern populations possess more realised load than masked load, possibly resulting in a chronic loss of fitness. Integrating pedigree and genomic data, we underscore the role of breeding management in reducing recent inbreeding. Yet ongoing heterozygosity loss, load accumulation, and persistent effects of historical inbreeding (i.e., background inbreeding) argue against the species' downlisting from its current Endangered status on the IUCN Red List and the Endangered Species Act. The presence of private genetic variation in wild and captive populations suggests that wild‐captive crosses could enhance genetic diversity and reduce the realised load. Our findings emphasise the role of genomics in informing conservation management and policy.

The role of leaf morphological plasticity in maintaining crown condition: A case study of London plane (Platanus x acerifolia) and valley oak (Quercus lobata) - Mickie Tang; Matthew E. Gilbert; Emily K. Meineke (Urban Forestry & Urban Greening, 2025)

Climate Consideration in Environmental Effects Analyses on Federal Public Lands in the United States - Sarah E. Whipple; Sarah K. Carter; Tait K. Rutherford; Samuel E. Jordan; Richard J. Lehrter; Christopher T. Domschke; Megan A. Gilbert; Julian Reyes; Ella M. Samuel; Karen M. Schank; John C. Tull; David J. A. Wood (Environmental Management, 2025)

Arctic lake trout ( Salvelinus namaycush ) show evidence of seasonal acclimation of cardiac adrenergic sensitivity but not heat tolerance - Emily P. Williams; Les N. Harris; Jean‐Sébastien Moore; Ella K. Middleton; Shira A. Berkelhammer; Ben Speers‐Roesch; Matthew J. H. Gilbert (Journal of Fish Biology, 2025)
Many Arctic fishes experience prolonged periods of extreme cold and large thermal variation over both rapid and seasonal time scales which challenge critical physiological functions. In the central Canadian Arctic, we caught wild adult lake trout ( Salvelinus namaycush ) acclimatized to winter and summer temperatures to determine the extent to which they seasonally adjust cardiac thermal performance and adrenergic control. We assessed the intrinsic and maximum heart rate ( f Hint and f Hmax ) of anaesthetised fish through cholinergic blockade and either adrenergic blockade ( f Hint ) or stimulation ( f Hmax ) during acute warming. Contrary to expectations, S. namaycush showed largely consistent heart rate responses to acute warming between seasons and adrenergic treatments. The f Hmax increased with acute warming and reached a peak (peak f H ) of 83 and 93 beats min −1 at temperatures ( T peak ) of 19.6 and 20°C and arrhythmia occurred at temperatures ( T arr ) of 22.7 and 22.3°C in winter and summer, respectively. However, in the winter, adrenergic stimulation was important to achieve peak f H at high temperatures; adrenergic blockade in winter did not affect T peak (18.3°C) or T arr (21°C) but lowered peak f H to only 68 beats min −1 ( p f H , when compared at common, cool to moderate temperatures, winter acclimated fish did exhibit slower atrioventricular conduction (longer PR interval), slower ventricular depolarization (longer QRS duration) and a shorter overall systolic duration (lower QT interval). Overall, S. namaycush exhibited no seasonal plasticity in cardiac thermal tolerance and modest seasonal changes in adrenergic control at high temperatures and in cardiac electrical activity. This limited thermal plasticity may constrain their ability to cope with seasonally distinct thermal challenges including extreme heat events and increase their reliance on other coping or avoidance mechanisms when thermal refugia are available (e.g. behavioural thermoregulation). An increased need for avoidance behaviour could limit the accessibility of key habit for foraging and spawning which occurs in late summer in this region (Dubos et al., 2024).

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Targeting the redox neuroinflammatory nexus: insights into Alzheimer’s and Parkinson’s diseases - Loganathan Chandramani Priya Dharshini; Kunnathur Murugesan Sakthivel; K. Gilbert Ross Rex; Rajan Radha Rasmi (Inflammopharmacology, 2025)

A high dietary protein level or poorly digestible protein source may lower voluntary feed intake and limit pre-cecal digesta flow and cecal protein fermentation in broilers - Miranda L. Elling-Staats; Arie K. Kies; Myrthe S. Gilbert; René P. Kwakkel (Animal Feed Science and Technology, 2025)

Effects of temperature and nutrient load on the interaction of Vibrio parahaemolyticus and plastic pollution in the marine environment - Kara J. Wiggin; Ryan K. Chung; Jack A. Gilbert; Sarah M. Allard (Marine Pollution Bulletin, 2025)

The potential of oviduct tags and fine‐scale acoustic telemetry to reveal the timing and location of spawning in Arctic salmonids ( Salvelinus spp.) - Véronique Dubos; Les N. Harris; Richard Ekpakohak; Brendan K. Malley; Matthew J. H. Gilbert; Nathan B. Furey; Jean‐Sébastien Moore (Journal of Fish Biology, 2025)
Identifying and characterizing spawning locations are paramount for the protection of critical fish habitats but can be challenging, particularly in remote locations. Using the underexplored oviduct‐tagging technique, we aimed to identify the timing and location of spawning for wild Arctic char ( Salvelinus alpinus ) and lake trout ( Salvelinus namaycush ) in two high‐Arctic lakes in Nunavut. Specifically, Innovasea V7 acoustic telemetry transmitters were inserted into the oviducts of 13 Arctic char and 4 lake trout, and the timing and location of tag expulsion were determined using a fine‐scale positioning system. Twenty Arctic char and 20 lake trout were also tagged with abdominal V16 transmitters, and 10 of them were paired with the oviduct tags, to further study the behavior of individual fish during the spawning season. Oviduct tags from four Arctic char and one lake trout could be used to assess the timing and location of spawning. Spawning anadromous Arctic char drastically reduced their activity and remained proximate to their presumed spawning location immediately before and for months after spawning. In contrast, a non‐anadromous (i.e., freshwater resident) Arctic char and a lake trout showed little to no reduction in activity around presumed spawning events. Because of the highlighted sedentary behavior of inferred spawning anadromous Arctic char implanted with both abdominal and oviduct tags, we could also infer potential spawning based on the behavior of individuals equipped only with abdominal tags. Spawning areas identified via telemetry also aligned well with Inuit knowledge of those lakes. This is the first field study to use acoustic oviduct and abdominal tags coupled with a fine‐scale positioning system. Despite a limited success rate of ejection, the study reveals the strong potential of the method to study spawning habitat and timing, particularly in remote areas.

A review of great ape behavioural responses and their outcomes to anthropogenic landscapes - Miranda A. Gilbert; Ammie K. Kalan (Primates, 2025)

Identifying Priority Science Information Needs for Managing Public Lands - Sarah K. Carter; Travis S. Haby; Ella M. Samuel; Alison C. Foster; Jennifer K. Meineke; Laine E. McCall; Malia K. Burton; Christopher T. Domschke; Leigh D. Espy; Megan A. Gilbert (Environmental Management, 2025)

An innovative approach to the multidisciplinary treatment of uninsured breast cancer patients - Jesse N. Nodora; Jacqueline A. Gilbert; Maria Elena Martinez; Waqas Arslan; Trevin Reyes; John A. Dover; Gilbert M. Ramos; Ian G. Komenaka; Hebert D. Hitchon; Ian K. Komenaka (Cancer Causes & Control, 2025)

Growth and metabolic performance of house fly and black soldier fly larvae differ across densities and waste-based growth substrates - Asmus Toftkær Muurmann; Niels Thomas Eriksen; Jacob Agerbo Rasmussen; Morten T. Limborg; Jeffery K. Tomberlin; M.Thomas P. Gilbert; Simon Bahrndorff (Waste Management, 2025)

Why Is It Too Cold? Towards a Mechanistic Understanding of Cold‐Water Pollution Effects on Recruitment of an Imperiled Warmwater Fish - Eliza I. Gilbert; Tracy A. Diver; Steven M. Mussmann; Melody J. Saltzgiver; William K. Knight; Scott L. Durst; Michael A. Farrington; Stephani L. Clark Barkalow; Michael Tobler; Nathan R. Franssen (Molecular Ecology, 2025)
Environmental temperature shapes the ontogeny of ectotherms by influencing rates of growth and development which can be key determinants of survival. Whereas the escalating impacts of water management on freshwater ecosystems is well documented, the effects of cold‐water releases from dams—which can alter downstream temperatures—remains relatively underexplored but may present novel challenges to endemic ectotherms. Specifically, little is known about how thermal depressions reshape phenotypic and genetic patterns during larval metamorphosis for fishes that evolved in warmwater systems. We assessed the effects of thermal shifts on larval ontogeny of the endangered razorback sucker ( Xyrauchen texanus ), which evolved in the warm waters of the Colorado River Basin, USA. We hypothesised that development is more sensitive to cold‐water influences than growth and that temperature would influence patterns in gene expression related to development. Our results supported these hypotheses and showed that both wild and laboratory‐reared larvae in slightly cooler temperatures exhibited delayed development, but similar growth compared to larvae reared in warmer conditions. These findings suggest growth and development in early ectotherm life stages can be decoupled, which follows patterns more like the temperature‐size rule than allometric scaling of development by size. We also observed transcriptional differences related to genes associated with stress responses and development in our laboratory‐reared fish; here, gene expression of fish from the coldest conditions at the end of the experiment was more similar to fish reared in warmer temperatures at the midpoint. Our findings suggest that modest temperature reductions can delay ontogeny and alter the transcriptional landscape while not necessarily limiting growth. This finding highlights the need for conservation practitioners to consider cascading impacts that even small temperature reductions can cause in riverine ecosystems.

Real-time in vivo confocal laser endomicroscopic imaging of equine endometrium: Preliminary observations and feasibility study - K. Gallacher; L. Woolford; L.C. Santos; P.B.S. Serpa; J. Len; R.O. Gilbert; K.L. Kind (The Veterinary Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Position-specific and clumped isotope equilibria in propane: Ab initio calculations beyond the harmonic and Born-Oppenheimer approximations - Xinya Yin; Yining Zhang; Qi Liu; Alexis Gilbert; Feixiang Liu; Caihong Gao; Siting Zhang; Moira K. Ridley; Yun Liu (Chemical Geology, 2024)

Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; K. Marie McIntyre; Philip Rasmussen; William Gilbert; Gemma Chaters; Kassy Raymond; Wudu T. Jemberu; Andrew Larkins; Grace T. Patterson; Stephen Kwok; Alexander James Kappes; Dianne Mayberry; et al. (Research in Veterinary Science, 2024)

Development of a culturally targeted chatbot to inform living kidney donor candidates of African ancestry about APOL1 genetic testing: a mixed methods study - Elisa J. Gordon; Jessica Gacki-Smith; Matthew J. Gooden; Preeya Waite; Rochell Yacat; Zenab R. Abubakari; Debra Duquette; Akansha Agrawal; John Friedewald; Sarah K. Savage; Matthew Cooper; Alexander Gilbert; et al. (Journal of Community Genetics, 2024)
Clinical chatbots are increasingly used to help integrate genetic testing into clinical contexts, but no chatbot exists for A polipoprotein L1 ( APOL1 ) genetic testing of living kidney donor (LKD) candidates of African ancestry. Our study aimed to culturally adapt and assess perceptions of the Gia® chatbot to help integrate APOL1 testing into LKD evaluation. Ten focus groups and post-focus group surveys were conducted with 54 LKDs, community members, and kidney transplant recipients of African ancestry. Data were analyzed through thematic analysis and descriptive statistics. Key themes about making Gia culturally targeted included ensuring: (1) transparency by providing Black LKDs’ testimonials, explaining patient privacy and confidentiality protections, and explaining how genetic testing can help LKD evaluation; (2) content is informative by educating Black LKDs about APOL1 testing instead of aiming to convince them to undergo testing, presenting statistics, and describing how genetic discrimination is legally prevented; and (3) content avoids stigma about living donation in the Black community. Most agreed Gia was neutral and unbiased (82%), trustworthy (82%), and words, phrases, and expressions were familiar to the intended audience (85%). Our culturally adapted APOL1 Gia chatbot was well regarded. Future research should assess how this chatbot could supplement provider discussion prior to genetic testing to scale APOL1 counseling and testing for LKD candidate clinical evaluation.

Rainfall-driven resuspension of pathogenic Leptospira in a leptospirosis hotspot - R. Thibeaux; P. Genthon; R. Govan; N. Selmaoui-Folcher; C. Tramier; M. Kainiu; M.-E. Soupé-Gilbert; K. Wijesuriya; C. Goarant (Science of The Total Environment, 2024)

Development of alginate beads for precise environmental release applications: A design of experiment based approach and analysis - P.U. Ashvin Iresh Fernando; Alan J. Kennedy; Kaytee Pokrzywinski; Johanna Jernberg; Travis Thornell; Garrett George; Gilbert K. Kosgei; Yanfei Wang; Kathryn J. Coyne (Journal of Environmental Management, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Approximating the global economic (market) value of farmed animals - Peggy Schrobback; Gabriel Dennis; Yin Li; Dianne Mayberry; Alexandra Shaw; Theodore Knight-Jones; Thomas Lloyd Marsh; Dustin L. Pendell; Paul R. Torgerson; William Gilbert; Benjamin Huntington; Kassy Raymond; et al. (Global Food Security, 2023)

An optimized radioimmunoassay for quantification of total serum thyroxine (T4) in fetal, neonatal, and pregnant rats - Katherine L. O'Shaughnessy; Michelle G. Hotchkiss; Angela K. Buckalew; Ashley S. Murr; Mary E. Gilbert; Tammy E. Stoker (Neurotoxicology and Teratology, 2023)

Associations between behavioral self-regulation and external food cue responsiveness (EFCR) in preschool-age children and evidence of modification by parenting style - Dabin Yeum; Diane Gilbert-Diamond; Travis D. Masterson; Delaina D. Carlson; Grace A. Ballarino; Reina K. Lansigan; Timothy J. Renier; Jennifer A. Emond (Appetite, 2023)

Stormwater Suspended Solids and Pollutant Concentrations in an Urban Stream - K. Spence; I. Gilbert; M. Robson (Water, Air, & Soil Pollution, 2023)
The chemical and ecological quality of small rivers or streams is not normally classified, but any urban stormwater discharges will result in their impairment. To assist in understanding the resulting applied environmental stress to benthic communities, the empirical relationships between in-stream suspended solids and metal pollutants, initially identified by principal component analysis, are explored using data from a small urbanised upland catchment. When data are amalgamated from individual storms, a correlation for each metal pollutant with suspended solids is obtained, starting very strongly, and decreasing in the order Fe > Al > Mn > Pb > Cr > Zn > Cu > Ni. Comparison of pollutant/solids correlations for individual storms is, for some metals, excellent, but differing intercepts and/or gradients can be obtained for an individual metal between storms. The practice of assessing their correlation based on event mean concentrations or longer-term averages across several storm events may conceal strong correlations for individual storms, exemplifying the impact of variable catchment characteristics and storm conditions; Cd and Be are poorly correlated with suspended solids and are likely affected by changes in background pollution levels. The analysis of covariance also highlights a significant difference between certain storm events for specific metals, which calls into question the validity of using combined storm-event datasets. The relationships identified here enable the determination of stormwater pollutant loads from suspended solids concentrations for heavy metals and are useful for developing water quality assessments.

Book review - Barrie K. Gilbert (Biological Conservation, 2023)

Integration of Biorelevant Pediatric Dissolution Methodology into PBPK Modeling to Predict In Vivo Performance and Bioequivalence of Generic Drugs in Pediatric Populations: a Carbamazepine Case Study - Gopal Pawar; Fang Wu; Liang Zhao; Lanyan Fang; Gilbert J. Burckart; Kairui Feng; Youssef M. Mousa; Abdullah Al Shoyaib; Marie-Christine Jones; Hannah K. Batchelor (The AAPS Journal, 2023)
This study investigated the impact of gastro-intestinal fluid volume and bile salt (BS) concentration on the dissolution of carbamazepine (CBZ) immediate release (IR) 100 mg tablets and to integrate these in vitro biorelevant dissolution profiles into physiologically based pharmacokinetic modelling (PBPK) in pediatric and adult populations to determine the biopredictive dissolution profile. Dissolution profiles of CBZ IR tablets (100 mg) were generated in 50–900 mL biorelevant adult fasted state simulated gastric and intestinal fluid (Ad-FaSSGF and Ad-FaSSIF), also in three alternative compositions of biorelevant pediatric FaSSGF and FaSSIF medias at 200 mL. This study found that CBZ dissolution was poorly sensitive to changes in the composition of the biorelevant media, where dissimilar dissolution (F2 = 46.2) was only observed when the BS concentration was changed from 3000 to 89 μM (Ad-FaSSIF vs Ped-FaSSIF 50% 14 BS). PBPK modeling demonstrated the most predictive dissolution volume and media composition to forecast the PK was 500 mL of Ad-FaSSGF/Ad-FaSSIF media for adults and 200 mL Ped-FaSSGF/FaSSIF media for pediatrics. A virtual bioequivalence simulation was conducted by using Ad-FaSSGF and/or Ad-FaSSIF 500 mL or Ped-FaSSGF and/or Ped-FaSSIF 200 mL dissolution data for CBZ 100 mg (reference and generic test) IR product. The CBZ PBPK models showed bioequivalence of the product. This study demonstrates that the integration of biorelevant dissolution data can predict the PK profile of a poorly soluble drug in both populations. Further work using more pediatric drug products is needed to verify biorelevant dissolution data to predict the in vivo performance in pediatrics. Graphical Abstract

In vitro reduction of Escherichia coli biofilm mass by platelet-rich plasma lysate (PRP-L) - Bryan C Stallings; Jessica Gilbert; Megan E Jacob; Lauren V Schnabel; Jose Len; Sara K Lyle (Journal of Equine Veterinary Science, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

Limited recovery following a massive seagrass decline in subarctic eastern Canada - Mélanie‐Louise Leblanc; Mary I. O'Connor; Zou Zou A. Kuzyk; Fanny Noisette; Kaleigh E. Davis; Ernie Rabbitskin; Laura‐Lee Sam; Urs Neumeier; Rémi Costanzo; Jens K. Ehn; David Babb; C. Julián Idrobo; et al. (Global Change Biology, 2023)
Over the last few decades, there has been an increasing recognition for seagrasses' contribution to the functioning of nearshore ecosystems and climate change mitigation. Nevertheless, seagrass ecosystems have been deteriorating globally at an accelerating rate during recent decades. In 2017, research into the condition of eelgrass ( Zostera marina ) along the eastern coast of James Bay, Canada, was initiated in response to reports of eelgrass decline by the Cree First Nations of Eeyou Istchee. As part of this research, we compiled and analyzed two decades of eelgrass cover data and three decades of eelgrass monitoring data (biomass and density) to detect changes and assess possible environmental drivers. We detected a major decline in eelgrass condition between 1995 and 1999, which encompassed the entire east coast of James Bay. Surveys conducted in 2019 and 2020 indicated limited changes post‐decline, for example, low eelgrass cover ( 50% cover in eastern James Bay since 1995, representing the largest scale eelgrass decline documented in eastern Canada since the massive die‐off event that occurred in the 1930s along the North Atlantic coast. Using biomass data collected since 1982, but geographically limited to the sector of the coast near the regulated La Grande River, generalized additive modeling revealed eelgrass meadows are affected by local sea surface temperature, early ice breakup, and higher summer freshwater discharge. Our results caution against assuming subarctic seagrass ecosystems have avoided recent global declines or will benefit from ongoing climate warming.

Determining resource intake of a nonnative fish highlights potential predatory and competitive interactions - S. C. Hedden; K. B. Gido; C. K. Hedden; C. A. Pennock; B. R. Duran; B. A. Hines; E. I. Gilbert; M. C. McKinstry; S. L. Durst; N. R. Franssen (Biological Invasions, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Future climate and its impact on streamflow: a case study of the Brahmaputra river basin - Pulendra Dutta; Gilbert Hinge; Jeffrey Denzil K. Marak; Arup Kumar Sarma (Modeling Earth Systems and Environment, 2021)

Urban American Indian Community Health Beliefs Associated with Addressing Cancer in the Northern Plains Region - Regina Idoate; Mark Gilbert; Keyonna M. King; Lisa Spellman; Bobbie McWilliams; Brittany Strong; Liliana Bronner; Mohammad Siahpush; Athena K. Ramos; Martina Clarke; Tzeyu Michaud; Maurice Godfrey; et al. (Journal of Cancer Education, 2021)

Gastro-intestinal parasitism and control practices in dairy cattle in North-west Cameroon (Central Africa) - Marc K. Kouam; Gilbert T. Fokom; Deguy D.’or N. Luogbou; Vaia Kantzoura (Acta Parasitologica, 2021)

Does a Trawl Ban Benefit Commercially Important Decapoda and Stomatopoda in Hong Kong? - Lily S. R. Tao; Gilbert C. S. Lui; Kingsley J. H. Wong; Tommy T. Y. Hui; Yanny K. Y. Mak; Ronia C.-t Sham; Jason K. C. Yau; William W. L. Cheung; Kenneth M. Y. Leung (Ecosystems, 2021)
Crustaceans were among the most valuable fishery resources in Hong Kong. However, the unrestricted and intensive use of different fishing gears, especially bottom trawling, has led to the depletion of commercially important crustaceans in Hong Kong since the 1980s. This study investigated whether commercial crustaceans recovered after the implementation of a permanent Hong Kong-wide trawl ban that began on December 31, 2012. Standardized field surveys were conducted using a commercial shrimp trawler at two sites in eastern and western waters of Hong Kong before (2004) and after the trawl ban (2013–2014 and 2015–2016) and two sites in southern waters after the trawl ban. Diversity, mean size, abundance, biomass and level of disturbance of commercial crustaceans from the three periods were investigated. The eastern waters exhibited an increased diversity of crustacean assemblages in Inner Tolo, and a higher abundance and biomass of crabs were detected in Outer Tolo after the trawl ban. Reduced disturbance, higher diversity in crustacean assemblages and greater abundance and biomass of predatory crabs were observed after the trawl ban in the outer estuary of western waters, and increased abundance and biomass of shrimp were detected in the inner estuary of western waters. No temporal or negative changes were detected in the southeast and southern waters of Lamma Island. The various responses of crustacean assemblages in Hong Kong waters revealed the critical role of complex interactions among multiple stresses, such as ongoing reclamation works, illegal trawling activities and increased fishing efforts using other (legal) fishing methods.

EXPRESSION OF CONCERN: InsectChange: a global database of temporal changes in insect and arachnid assemblages - Roel van Klink; Diana E. Bowler; Orr Comay; Michael M. Driessen; S. K. Morgan Ernest; Alessandro Gentile; Francis Gilbert; Konstantin B. Gongalsky; Jennifer Owen; Guy Pe'er; Israel Pe'er; Vincent H. Resh; et al. (Ecology, 2021)
Insects are the most ubiquitous and diverse group of eukaryotic organisms on Earth, forming a crucial link in terrestrial and freshwater food webs. They have recently become the subject of headlines because of observations of dramatic declines in some places. Although there are hundreds of long‐term insect monitoring programs, a global database for long‐term data on insect assemblages has so far remained unavailable. In order to facilitate synthetic analyses of insect abundance changes, we compiled a database of long‐term (≥10 yr) studies of assemblages of insects (many also including arachnids) in the terrestrial and freshwater realms. We searched the scientific literature and public repositories for data on insect and arachnid monitoring using standardized protocols over a time span of 10 yr or longer, with at least two sampling events. We focused on studies that presented or allowed calculation of total community abundance or biomass. We extracted data from tables, figures, and appendices, and, for data sets that provided raw data, we standardized trapping effort over space and time when necessary. For each site, we extracted provenance details (such as country, state, and continent) as well as information on protection status, land use, and climatic details from publicly available GIS sources. In all, the database contains 1,668 plot‐level time series sourced from 165 studies with samples collected between 1925 and 2018. Sixteen data sets provided here were previously unpublished. Studies were separated into those collected in the terrestrial realm (103 studies with a total of 1,053 plots) and those collected in the freshwater realm (62 studies with 615 plots). Most studies were from Europe (48%) and North America (29%), with 34% of the plots located in protected areas. The median monitoring time span was 19 yr, with 12 sampling years. The number of individuals was reported in 129 studies, the total biomass was reported in 13 studies, and both abundance and biomass were reported in 23 studies. This data set is published under a CC‐BY license, requiring attribution of the data source. Please cite this paper if the data are used in publications, and respect the licenses of the original sources when using (part of) their data as detailed in Metadata S1: Table 1.

Development of a Pediatric Relative Bioavailability/Bioequivalence Database and Identification of Putative Risk Factors Associated With Evaluation of Pediatric Oral Products - Gopal Pawar; Fang Wu; Liang Zhao; Lanyan Fang; Gilbert J. Burckart; Kairui Feng; Youssef M. Mousa; Franci Naumann; Hannah K. Batchelor (The AAPS Journal, 2021)
Generally, bioequivalence (BE) studies of drug products for pediatric patients are conducted in adults due to ethical reasons. Given the lack of direct BE assessment in pediatric populations, the aim of this work is to develop a database of BE and relative bioavailability (relative BA) studies conducted in pediatric populations and to enable the identification of risk factors associated with certain drug substances or products that may lead to failed BE or different pharmacokinetic (PK) parameters in relative BA studies in pediatrics. A literature search from 1965 to 2020 was conducted in PubMed, Cochrane Library, and Google Scholar to identify BE studies conducted in pediatric populations and relative BA studies conducted in pediatric populations. Overall, 79 studies covering 37 active pharmaceutical ingredients (APIs) were included in the database: 4 bioequivalence studies with data that passed BE evaluations; 2 studies showed bioinequivalence results; 34 relative BA studies showing comparable PK parameters, and 39 relative BA studies showing differences in PK parameters between test and reference products. Based on the above studies, common putative risk factors associated with differences in relative bioavailability (DRBA) in pediatric populations include age-related absorption effects, high inter-individual variability, and poor study design. A database containing 79 clinical studies on BE or relative BA in pediatrics has been developed. Putative risk factors associated with DRBA in pediatric populations are summarized.

Arsenic Exposure in Relation to Apple Consumption Among Infants in the New Hampshire Birth Cohort Study - A. J. Signes-Pastor; T. Punshon; K. L. Cottingham; B. P. Jackson; V. Sayarath; D. Gilbert-Diamond; S. Korrick; M. R. Karagas (Exposure and Health, 2020)

Anadromy and marine habitat use of Lake trout ( Salvelinus namaycush ) from the central Canadian Arctic - Les N. Harris; Heidi K. Swanson; Matthew J.H. Gilbert; Brendan K. Malley; Aaron T. Fisk; Jean‐Sébastien Moore (Journal of Fish Biology, 2020)
Anadromy was documented in 16 lake trout, Salvelinus namaycush , from Canada's central Arctic using capture data and otolith microchemistry. For the first time, estuarine/marine habitat use was described for five individuals using acoustic telemetry. Age‐at‐first‐migration to sea was variable (10–39 years) among individuals and most S. namaycush undertook multiple anadromous migrations within their lifetime. Telemetry data suggested that S. namaycush do not travel far into marine habitats and prefer surface waters ( S. namaycush .

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Effects of the Bioturbating Marine Yabby Trypaea australiensis on Sediment Properties in Sandy Sediments Receiving Mangrove Leaf Litter - Ryan J. K. Dunn; David T. Welsh; Peter R. Teasdale; Franck Gilbert; Jean-Christophe Poggiale; Nathan J. Waltham (Journal of Marine Science and Engineering, 2019)
Laboratory mesocosm incubations were undertaken to investigate the influence of burrowing shrimp Trypaea australiensis (marine yabby) on sediment reworking, physical and chemical sediment characteristics and nutrients in sandy sediments receiving mangrove (Avicennia marina) leaf litter. Mesocosms of sieved, natural T. australiensis inhabited sands, were continually flushed with fresh seawater and pre-incubated for 17 days prior to triplicates being assigned to one of four treatments; sandy sediment (S), sediment + yabbies (S+Y), sediment + leaf litter (organic matter; S+OM) and sediment + yabbies + leaf litter (S+Y+OM) and maintained for 55 days. Mangrove leaf litter was added daily to treatments S+OM and S+Y+OM. Luminophores were added to mesocosms to quantify sediment reworking. Sediment samples were collected after the pre-incubation period from a set of triplicate mesocosms to establish initial conditions prior to the imposition of the treatments and from the treatment mesocosms at the conclusion of the 55-day incubation period. Yabbies demonstrated a clear effect on sediment topography and leaf litter burial through burrow creation and maintenance, creating mounds on the sediment surface ranging in diameter from 3.4 to 12 cm. Within S+Y+OM sediments leaf litter was consistently removed from the surface to sub-surface layers with only 7.5% ± 3.6% of the total mass of leaf detritus added to the mesocosms remaining at the surface at the end of the 55-day incubation period. Yabbies significantly decreased sediment wet-bulk density and increased porosity. Additionally, T. australiensis significantly reduced sediment bio-available ammonium (NH4+bio) concentrations and altered the shape of the concentration depth profile in comparison to the non-bioturbated mesocosms, indicating influences on nutrient cycling and sediment-water fluxes. No significant changes for mean apparent biodiffusion coefficients (Db) and mean biotransport coefficients (r), were found between the bioturbated S+Y and S+Y+OM mesocosms. The findings of this study provide further evidence that T. australiensis is a key-species in shallow intertidal systems playing an important role as an ‘ecosystem engineer’ in soft-bottom habitats by significantly altering physical and chemical structures and biogeochemical function.

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

RNA interference-based silencing of the alpha-amylase (amy1) gene in Aspergillus flavus decreases fungal growth and aflatoxin production in maize kernels - Matthew K. Gilbert; Rajtilak Majumdar; Kanniah Rajasekaran; Zhi-Yuan Chen; Qijian Wei; Christine M. Sickler; Matthew D. Lebar; Jeffrey W. Cary; Bronwyn R. Frame; Kan Wang (Planta, 2018)

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Effects of lipophilicity, protecting group and stereochemistry on the antimalarial activity of carbohydrate-derived thiochromans - Gilbert K. Madumo; Paseka T. Moshapo; Henok H. Kinfe (Medicinal Chemistry Research, 2018)

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Hong Kong’s rich marine biodiversity: the unseen wealth of South China’s megalopolis - Terence P. T. Ng; Martin C. F. Cheng; Kevin K. Y. Ho; Gilbert C. S. Lui; Kenneth M. Y. Leung; Gray A. Williams (Biodiversity and Conservation, 2017)

First recorded case of tiger killing Eurasian lynx - Yuri K. Petrunenko; Ivan L. Polkovnikov; Martin Gilbert; Dale G. Miquelle (European Journal of Wildlife Research, 2016)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Deriving field-based sediment quality guidelines from the relationship between species density and contaminant level using a novel nonparametric empirical Bayesian approach - Gilbert C. S. Lui; W. K. Li; Anders Bjørgesæter; Kenneth M. Y. Leung (Environmental Science and Pollution Research, 2014)

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Mind the gap: the ratio of yolk androgens and antioxidants varies between sons and daughters dependent on paternal attractiveness - E. C. Pariser; L. Gilbert; N. Hazon; K. E. Arnold; J. A. Graves (Behavioral Ecology and Sociobiology, 2012)

Natural outbreak of Streptococcus agalactiae (GBS) infection in wild giant Queensland grouper, Epinephelus lanceolatus (Bloch), and other wild fish in northern Queensland, Australia - R O Bowater; J Forbes‐Faulkner; I G Anderson; K Condon; B Robinson; F Kong; G L Gilbert; A Reynolds; S Hyland; G McPherson; J O’ Brien; D Blyde (Journal of Fish Diseases, 2012)
Ninety‐three giant Queensland grouper, Epinephelus lanceolatus (Bloch), were found dead in Queensland, Australia, from 2007 to 2011. Most dead fish occurred in northern Queensland, with a peak of mortalities in Cairns in June 2008. In 2009, sick wild fish including giant sea catfish, Arius thalassinus (Rüppell), and javelin grunter, Pomadasys kaakan (Cuvier), also occurred in Cairns. In 2009 and 2010, two disease epizootics involving wild stingrays occurred at Sea World marine aquarium. Necropsy, histopathology, bacteriology and PCR determined that the cause of deaths of 12 giant Queensland grouper, three wild fish, six estuary rays, Dasyatis fluviorum (Ogilby), one mangrove whipray, Himantura granulata (Macleay), and one eastern shovelnose ray, Aptychotrema rostrata (Shaw), was Streptococcus agalactiae septicaemia. Biochemical testing of 34 S. agalactiae isolates from giant Queensland grouper, wild fish and stingrays showed all had identical biochemical profiles. The 16S rRNA gene sequences of isolates confirmed all isolates were S. agalactiae ; genotyping of selected S. agalactiae isolates showed the isolates from giant Queensland grouper were serotype Ib, whereas isolates from wild fish and stingrays closely resembled serotype II. This is the first report of S. agalactiae from wild giant Queensland grouper and other wild tropical fish and stingray species in Queensland, Australia.

Mitochondrial Haplogroup X is associated with successful aging in the Amish - Monique D. Courtenay; John R. Gilbert; Lan Jiang; Anna C. Cummings; Paul J. Gallins; Laura Caywood; Lori Reinhart-Mercer; Denise Fuzzell; Claire Knebusch; Renee Laux; Jacob L. McCauley; Charles E. Jackson; et al. (Human Genetics, 2012)

Variation in wind and piscivorous predator fields affecting the survival of Atlantic salmon, Salmo salar , in the Gulf of Maine - K. D. FRIEDLAND; J. P. MANNING; J. S. LINK; J. R. GILBERT; A. T. GILBERT; A. F. O’CONNELL (Fisheries Management and Ecology, 2012)
Observations relevant to the North American stock complex of Atlantic salmon, Salmo salar L., suggest that marine mortality is influenced by variation in predation pressure affecting post‐smolts during the first months at sea. This hypothesis was tested for Gulf of Maine (GOM) stocks by examining wind pseudostress and the distribution of piscivorous predator fields potentially affecting post‐smolts. Marine survival has declined over recent decades with a change in the direction of spring winds, which is likely extending the migration of post‐smolts by favouring routes using the western GOM. In addition to changes in spring wind patterns, higher spring sea surface temperatures have been associated with shifting distributions of a range of fish species. The abundance of several pelagic piscivores, which based on their feeding habits may predate on salmon post‐smolts, has increased in the areas that serve as migration corridors for post‐smolts. In particular, populations of silver hake, Merluccius bilinearis (Mitchell), red hake, Urophycis chuss (Walbaum), and spiny dogfish, Squalus acanthias L., increased in size in the portion of the GOM used by post‐smolts. Climate variation and shifting predator distributions in the GOM are consistent with the predator hypothesis of recruitment control suggested for the stock complex.

Omics for understanding microbial functional dynamics - Janet K. Jansson; Josh D. Neufeld; Mary Ann Moran; Jack A Gilbert (Environmental Microbiology, 2012)

Erratum to: Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Translational Biomarkers: from Preclinical to Clinical a Report of 2009 AAPS/ACCP Biomarker Workshop - Jane P. F. Bai; Robert Bell; ShaAvhree Buckman; Gilbert J. Burckart; Hans-Georg Eichler; Kenneth C. Fang; Federico M. Goodsaid; William J. Jusko; Lawrence L. Lesko; Bernd Meibohm; Scott D. Patterson; Oscar Puig; et al. (The AAPS Journal, 2011)

Cultural Influences on Safety and Health Education Among Vietnamese Fishermen - Ann K. Carruth; Jeffrey L. Levin; Karen Gilmore; Thu Bui; Gilbert Gallardo; William Evert; Lorinda Sealey (Journal of Agromedicine, 2010)

Combining Ecological Classification Systems and Conservation Filters Could Facilitate the Integration of Wildlife and Forest Management - Eric K. Zenner; JeriLynn E. Peck; Kristen Brubaker; Benjamin Gamble; Carrie Gilbert; Daniel Heggenstaller; Jeanne Hickey; Kelly Sitch; Robbie Withington (Journal of Forestry, 2010)
Ecosystem management demands simultaneous consideration and integration of ecosystem services in monitoring, planning, and management activities, but specialization has led to independently developed traditions in wildlife biology and management and forestry. We drew on the literature to explore the use of filters in wildlife conservation and ecological classification systems in forest management and to ask the question, “Can combining these tools improve our integration of wildlife and forest management?” Although each tool has been successfully applied independently, relatively few examples still exist for their combined use. We conclude that this approach has potential for enhancing research, monitoring, and management in areas beyond wildlife management, including forest health.

Nitrogen in soils, plants, surface water and shallow groundwater in a bahiagrass pasture of Southern Florida, USA - Gilbert C. Sigua; Robert K. Hubbard; Samuel W. Coleman; Mimi Williams (Nutrient Cycling in Agroecosystems, 2010)

Variants in toll-like receptors 2 and 9 influence susceptibility to pulmonary tuberculosis in Caucasians, African-Americans, and West Africans - Digna Rosa Velez; Christian Wejse; Martin E. Stryjewski; Eduardo Abbate; William F. Hulme; Jamie L. Myers; Rosa Estevan; Sara G. Patillo; Rikke Olesen; Alessandra Tacconelli; Giorgio Sirugo; John R. Gilbert; et al. (Human Genetics, 2010)

Quantifying phosphorus levels in soils, plants, surface water, and shallow groundwater associated with bahiagrass-based pastures - Gilbert C. Sigua; Robert K. Hubbard; Samuel W. Coleman (Environmental Science and Pollution Research, 2010)

NOS2A, TLR4, and IFNGR1 interactions influence pulmonary tuberculosis susceptibility in African-Americans - Digna Rosa Velez; William F. Hulme; Jamie L. Myers; J. Brice Weinberg; Marc C. Levesque; Martin E. Stryjewski; Eduardo Abbate; Rosa Estevan; Sara G. Patillo; John R. Gilbert; Carol D. Hamilton; William K. Scott (Human Genetics, 2009)

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Glaciolacustrine varved sediment as an alpine hydroclimatic proxy - K. R. Hodder; R. Gilbert; J. R. Desloges (Journal of Paleolimnology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

First observation of the giant clam Tridacna squamosa in French Polynesia: a species range extension - A. Gilbert; S. Planes; S. Andréfouët; K. Friedman; G. Remoissenet (Coral Reefs, 2007)

Temporal variation in the expression of the p53 protein in proliferating and differentiating murine erythroleukaemia cells - U. M. Bodalina; K. D. Hammond; D. A. Gilbert (Molecular and Cellular Biochemistry, 2007)

Snow-contact volcanic facies and their use in determining past eruptive environments at Nevados de Chillán volcano, Chile - K. Mee; H. Tuffen; J. S. Gilbert (Bulletin of Volcanology, 2006)

Maternal mosaicism for mutations in the ARX gene in a family with X linked mental retardation - K. Poirier; J. Abriol; I. Souville; C. Laroche-Raynaud; C. Beldjord; B. Gilbert; J. Chelly; T. Bienvenu (Human Genetics, 2005)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

Points of View - BARRIE K. GILBERT (Conservation Biology, 2004)

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

A high degree of genetic diversity is revealed in Isatis spp. (dyer's woad) by amplified fragment length polymorphism (AFLP) - K. Gilbert; S. Garton; M. Karam; G. Arnold; A. Karp; K. Edwards; D. Cooke; J. Barker (Theoretical and Applied Genetics, 2002)

Measuring life‐history omnivory in the opossum shrimp, Mysis relicta, with stable nitrogen isotopes - Donn K. Branstrator; Gilbert Cabana; Asit Mazumder; Joseph B. Rasmussen (Limnology and Oceanography, 2000)
Mysis relicta is a species of omnivorous zooplankton that has been implicated over the last several decades in important food‐web processes such as the lengthening of food chains, the mobilization of benthic contaminants to the pelagic, and the restructuring of community dynamics. We used stable nitrogen isotopes (δ 15 N) to quantify ontogenetic diet shifting of M. relicta in five North American lakes. Analyses indicated that M. relicta measuring >1.5 cm were elevated, on average, 0.73 trophic levels above conspecifics measuring 1.5‐cm length. This pattern suggests a trend toward increasing carnivory with maturity, which is consistent with the results of previous conventional approaches to diet analysis in this species. Our results should be useful to modelers concerned with quantifying the effects of M. relicta on energy transfer and contaminant bioaccumulation in food chains.

Identification of the key factors affecting composting of a weathered hydrocarbon-contaminated soil - A.U. Nwankwoala; N.O. Egiebor; c. Gilbert; K. Nyavor (Biodegradation, 1999)

Influence of The D Genome in Fusarium Head Blight Resistance - J. Gilbert; T. Aung; J. D. Procunier K (Cereal Research Communications, 1997)

Wide Crosses to Improve Fusarium Blight Resistance in Wheat - George Fedak; K. C. Armstrong; R. C. Sinha; J. Gilbert; J. D. Procunier; J. D. Miller; R. Pandeya (Cereal Research Communications, 1997)

Eyes absent: A gene family found in several metazoan phyla - Melinda K. Duncan; Lidia Kos; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Stanislav I. Tomarev (Mammalian Genome, 1997)

cDNA cloning and chromosomal mapping of mouse fast skeletal muscle troponin T - Anne Koch; Todd S. -C. Juan; Nancy A. Jenkins; Debra J. Gilbert; Neal G. Copeland; Ian K. McNiece; Frederick A. Fletcher (Mammalian Genome, 1997)

Linkage of acetylcholinesterase insensitivity to methyl parathion resistance inHeliothis virescens - Robert D. Gilbert; Patricia K. Bryson; Thomas M. Brown (Biochemical Genetics, 1996)

Linkage of acetylcholinesterase insensitivity to methyl parathion resistance inHeliothis virescens - Robert D. Gilbert; Patricia K. Bryson; Thomas M. Brown (Biochemical Genetics, 1996)

Mechanism of entry of a xenotropic MMuLV-derived recombinant retrovirus into porcine cells using the expression of the reporternlslacZ gene - M. A. Gilbert; B. Charreau; P. Vicart; D. Paulin; P. K. Nandi (Archives of Virology, 1992)

ThePassiflora problem in Hawaii; prospects and problems of controlling the forest weedP. Mollissima [Passifloraceae] with heliconiine butterflies - J. K. Waage; J. T. Smiley; L. E. Gilbert (BioControl, 1981)

Genetic variability for regional brain gangliosides in five strains of young mice - Thomas N. Seyfried; Gilbert H. Glaser; Robert K. Yu (Biochemical Genetics, 1979)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)